KERAGAMANAN GENETIK DAN PERMUDAAN ALAM PUSPA (Schima wallichii (DC.) Korth.) DI TAMAN NASIONAL GUNUNG MERAPI PASCA ERUPSI MERAPI 2010 - Bangun Baramantya; Sapto Indrioko; Lies Rahayu Wijayanti Faida; Yayan Hadiyan (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Schima wallichii (DC.) Korth. (puspa) is a native vegetation of Gunung Merapi National Park (GMNP). This species has an important function for soil and water conservation in GMNP area, especially in the area with high slope. Puspa is also one of prioritised species planted in the forest ecosystem restoration project of GMNP after 2010 volcano eruption. Information on genetic diversity and natural regeneration potential of each puspa stand groups is then very essential for the success of forest ecosystem restoration in GMNP. Genetic diversity parameters of puspa is assessed by isozyme analysis, while its natural regeneration is evaluated by vegetation analysis. Selection of samples on stand groups of puspa for genetic diversity and natural regeneration analysis is based on levels of vegetation damage (low and moderate) and the planting plots of ecosystem restoration area. The results showed that the stands with low damage level located at Gunung Malang and Mriyan have higher genetic diversity than those with moderate damage level (Balerante and Tlogolele). Stand with the highest genetic diversity is Gunung Malang, with the mean observed heterozigosities (Ho) of 0.284 and minimum fixation index value (FIS) of 0.0508. Stand in the Ecosystem Restoration Demonstration Plot has the lowest level of genetic diversity (Ho = 0.1936; FIS = 0.1127). Regarding natural regeneration potential, the stand group of Gunung Malang is the highest.